The Influence of Site Visuals, Website Quality, and Perceived Product Benefits on Gen Z’s Purchase Decisions on TikTok - Andriya Riana Justitia; Sutono Sutono; Ag. Sunarno Handoyo Handoyo (Global Insights in Management and Economic Research, 2025)
Purpose of the study: The rapid evolution of social media platforms has transformed digital commerce, with TikTok emerging as a prominent social commerce platform. TikTok's integration of entertainment and shopping features has attracted significant attention from businesses, particularly in reaching Generation Z consumers who represent the platform's largest user demographic. This research investigates the role of site visuals, site quality, and product benefits in shaping Gen Z purchasing decisions on TikTok, with shopping experience as a mediating variable. The study specifically examines Le Skin Aesthetic Wonosobo consumers' behavior on the TikTok platform. Materials and methods: A quantitative approach using survey methodology was employed to collect data from 140 Gen Z consumers (aged 15-28 years) who made purchases through TikTok Shop during March-May 2025. Data were analyzed using Structural Equation Modeling (SEM) with AMOS 24.0 software. The research model examined five constructs: Site Visuals (X1), Site Quality (X2), Product Benefits (X3), Shopping Experience (Y1), and Purchase Decision (Y2), measured using validated multi-item scales. Results: Site Visuals (β=0.312, p<0.01) and Site Quality (β=0.384, p<0.001) demonstrated significant positive effects on Shopping Experience, collectively explaining 51.4% of its variance. Product Benefits exhibited the strongest direct effect on Purchase Decision (β=0.421, p<0.001). However, Site Visuals, Site Quality, and Shopping Experience showed no significant direct effects on Purchase Decision. Shopping Experience failed to mediate the relationships between exogenous variables and Purchase Decision. The overall model demonstrated excellent fit indices and explained 61.6% of variance in Purchase Decision. Conclusions: Gen Z consumers' purchase decisions on TikTok are primarily driven by tangible product benefits rather than site aesthetics or experiential factors. While site characteristics successfully shape the shopping experience, they do not translate into actual purchase behavior, revealing a notable disconnect between engagement and conversion in the social commerce context for skincare products.